2012
DOI: 10.1007/s00170-012-4491-7
|View full text |Cite
|
Sign up to set email alerts
|

RP part surface quality versus build orientation: when the layers are getting thinner

Abstract: Surface quality is a very important factor to be considered in determining part build orientation in rapid prototyping (RP) processes. Previous research has shown that parts built with inclined planes or curved surfaces along the build orientation have large staircase effect, thus have higher surface roughness compared to parts built with only vertical surfaces. However, as layers are getting thinner in rapid prototyping processes, the opposite might be true. In this study, a number of experiments and measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Chen et al [10] analyzed the surface quality of the cylindrical parts printed on the Objet EDEN 350 and observed some errors (rough surface areas) on a layer perpendicular to the scanning direction. These were caused by the lower resolution of 600 dots per inch (DPI) (0.042 mm) in the X -direction and Y -direction compared to 1600 DPI (0.016 mm) in the Z -direction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al [10] analyzed the surface quality of the cylindrical parts printed on the Objet EDEN 350 and observed some errors (rough surface areas) on a layer perpendicular to the scanning direction. These were caused by the lower resolution of 600 dots per inch (DPI) (0.042 mm) in the X -direction and Y -direction compared to 1600 DPI (0.016 mm) in the Z -direction.…”
Section: Resultsmentioning
confidence: 99%
“…However, Polyjet technology used on the EDEN 350 machine allows only deposition of thinner layers of 0.016 mm. In addition, Chen [10] concluded that, for very low thickness, the effect of change in layer thickness has a very low contribution toward change in surface roughness.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is advantageous to print a circular model that has holes standing up on the build platform, so support material does not fill the holes [38]. Additionally, if a circular model is lying down on the build platform and printed in glossy printing mode, then the surface quality is affected by some errors [41]. The experimental roughness (Ra) values for the PolyJet material jetting process are specified according to the finish type as follows: for matte finish in the range of 0.5-15 μm, and for the glossy finish in the range of 0.5-4 μm [42].…”
Section: Process Specifications Materials Artifact and Manufacturimentioning
confidence: 99%